Optimizing Smart Contracts and Blockchain for Sustainable Digital Fashionpreneurship - Santa Lusianna Sitorus; Ratna Tri Hari Safariningsih; Aldo Hermaya Aditiya Nur Karsa; Maulana Arif Komara; Richard Evans (IAIC Bangun Bangsa, 2025)
The digital fashion industry is undergoing a major transformation with the integration of technologies such as blockchain and smart contracts, which offer solutions to key challenges such as product authenticity, intellectual property protection, and supply chain efficiency. This research focuses on the application of blockchain technology and smart contracts in digital fashion entrepreneurship, with the aim of increasing transaction efficiency, product security, and business sustainability. Method used in this study is a quantitative approach with a structural model based on Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the influence between smart contract adoption, digital transaction efficiency, product security, and fashionpreneurship sustainability. Data were collected from digital fashion actors involved in the blockchain-based ecosystem. Research result shows that the adoption of smart contracts has a positive effect on transaction efficiency and product security. In addition, blockchain has been shown to increase supply chain transparency that supports the sustainability of digital fashion businesses. Although this technology faces technical challenges such as high transaction speed and costs, solutions such as layer-2 technology can improve blockchain performance. The conclusion blockchain and smart contract technology can be an effective solution in increasing efficiency, security, and sustainability in the digital fashion industry. Although there are technical challenges that need to be overcome, the application of this technology has great potential to create a more environmentally friendly and transparent digital fashion ecosystem.